2016
DOI: 10.1093/mnras/stw1602
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of GAMA galaxy halo masses on the cosmic web environment from 100 deg2of KiDS weak lensing data

Abstract: Galaxies and their dark matter haloes are part of a complex network of mass structures, collectively called the cosmic web. Using the tidal tensor prescription these structures can be classified into four cosmic environments: voids, sheets, filaments and knots. As the cosmic web may influence the formation and evolution of dark matter haloes and the galaxies they host, we aim to study the effect of these cosmic environments on the average mass of galactic haloes. To this end we measure the galaxy-galaxy lensin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 69 publications
1
18
0
Order By: Relevance
“…Nonetheless, a similar implementation, the DISPERSE code of Sousbie (2011), has been used by Duckworth et al (2019) to connect MaNGA galaxy kinematics to assembly history. An implementation of the deformation tensor method we used was also recently used on a sample of ∼ 10 5 galaxies from the GAMA survey (Eardley et al 2015;Brouwer et al 2016). This analysis lead to the conclusion that the galaxy mass function does not depend on the deformation tensor, but only on the large-scale overdensity.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, a similar implementation, the DISPERSE code of Sousbie (2011), has been used by Duckworth et al (2019) to connect MaNGA galaxy kinematics to assembly history. An implementation of the deformation tensor method we used was also recently used on a sample of ∼ 10 5 galaxies from the GAMA survey (Eardley et al 2015;Brouwer et al 2016). This analysis lead to the conclusion that the galaxy mass function does not depend on the deformation tensor, but only on the large-scale overdensity.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the "galactic conformity"-the observation that satellites are more likely to be quenched around quiescent centrals than star-forming (SF) ones-has been found on both small and larger megaparsec scales (Weinmann et al 2006;Kauffmann et al 2013;Hartley et al 2015;Hearin et al 2015;Berti et al 2017;Hatfield & Jarvis 2016;Kawinwanichakij et al 2016), suggesting the role of the large-scale gravitational tidal field on galaxy properties. Moreover, several observations have found that the star formation activity and other galaxy properties depend on the large-scale cosmic web (Fadda et al 2008;Porter et al 2008;Biviano et al 2011;Darvish et al 2014;Ricciardelli et al 2014;Chen et al 2016b;Darvish et al 2015a;Guo et al 2015;Alpaslan et al 2016;Pandey & Sarkar 2016), whereas others have seen no or at best a weak dependence between the properties of galaxies and the global cosmic web environments (Alpaslan et al 2015;Eardley et al 2015;Filho et al 2015;Penny et al 2015;Alonso et al 2016;Beygu et al 2016;Brouwer et al 2016;Vulcani et al 2016a).…”
Section: For Reviews)mentioning
confidence: 99%
“…The first two data releases from KiDS (de Jong et al 2015) became public in 2013 and 2015, containing reduced image data, source lists and a multi-band catalogue for a total of 148 survey tiles ( 160 deg 2 ). Based on this data set, the first scientific results focused on weak lensing studies of galaxies and galaxy A134, page 2 of 26 groups in the Galaxy And Mass Assembly (GAMA, Driver et al 2011) fields (Kuijken et al 2015;Sifón et al 2015;Viola et al 2015;Brouwer et al 2016;van Uitert et al 2016). Furthermore, these data releases were the basis for the first results from a z ∼ 6 quasar search (Venemans et al 2015), a catalogue of photometric redshifts from machine-learning (Cavuoti et al 2015(Cavuoti et al , 2017, preliminary results on super-compact massive galaxies (Tortora et al 2016), and a catalogue of galaxy clusters (Radovich et al 2017).…”
mentioning
confidence: 99%